Environmental enrichment protects the retina from early diabetic damage in adult rats - Dorfman, Damián (2014)
Diabetic retinopathy is a leading cause of reduced visual acuity and acquired blindness. Available treatments are not completely effective. We analyzed the effect of environmental enrichment on retinal damage induced by experimental diabetes in adult Wistar rats. Diabetes was induced by an intraperitoneal injection of streptozotocin. Three days after vehicle or streptozotocin injection, animals were housed in enriched environment or remained in a standard environment. Retinal function (electroretinogram, and oscillatory potentials), retinal morphology, blood-retinal barrier integrity, synaptophysin, astrocyte and Müller cell glial fibrillary acidic protein, vascular endothelial growth factor, tumor necrosis factor-α, and brain-derived neurotrophic factor levels, as well as lipid peroxidation were assessed in retina from diabetic animals housed in standard or enriched environment. Environmental enrichment preserved scotopic electroretinogram a-wave, b-wave and oscillatory potential amplitude, avoided albumin-Evan's blue leakage, prevented the decrease in retinal synaptophysin and astrocyte glial fibrillary acidic protein levels, the increase in Müller cell glial fibrillary acidic protein, vascular endothelial growth factor and tumor necrosis factor-α levels, as well as oxidative stress induced by diabetes. In addition, enriched environment prevented the decrease in retinal brain-derived neurotrophic factor levels induced by experimental diabetes. When environmental enrichment started 7 weeks after diabetes onset, retinal function was significantly preserved. These results indicate that enriched environment could attenuate the early diabetic damage in the retina from adult rats.